A study on factors contributing to students’ English pronunciation - Cholisah, Nur; Tresnadewi, Sintha; Yaniafari, Rahmati Putri (ELT Forum: Journal of English Language Teaching, 2021)
One of the most important things in learning English as a second language is pronunciation. Having good pronunciation can lead to a successful Speech communication. However, many students find it difficult in learning pronunciation. Many studies have already been conducted to dig in the difficulties and try to overcome the issue. In fact, there are still many students who have good pronunciation, yet not many researchers have conducted studies on how to dig in the factors contributing to it. This study aims at finding the factors that may contribute to the students’ good English pronunciation by applying a descriptive qualitative research design. Some instruments were used in collecting the data such as a pronunciation test, an observation checklist, a field note, and an interview guide. This study found that there were four big factors that contributed to the students’ English pronunciation: education, exposure, environment, and motivation. Each factor has made a powerful contribution to the subjects’ English pronunciation such as applying a reflective practice method, providing a lot of input about English, providing supportive family and friend, and providing a strong motivation to reach something. This study suggests that future researcher might use the pronunciation test with categorization of words in it.